Primordialisme dalam Pemilihan Presiden dan Caleg Bagi Pemilih Kritis di Tanjungpinang Barat - Tengku Ananda Sapphira; Pitriani Pitriani (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The Unitary State of the Republic of Indonesia lives with a pluralistic society. The existence of this pluralistic society indicates that Indonesia is filled with diversity. Starting from ethnic diversity, customs, culture, religion, and many more Again. This diversity shows that Indonesia needs a system democratic government, where every government process requires the people's contribution so that the people continue to live side by side even though they are filled with the essence A democratic country is a government of the people, by the people, and for the people. This means that the government exercises its power on behalf of the people. Therefore, Indonesia implementing an election system in determining leaders in Indonesia. However, in this election process there are ties of primordialism that influence how people determine their choices according to certain beliefs trusted. This research explores the existence of primordialism in elections in Indonesia, especially in West Tanjungpinang District, Tanjungpinang City. Researcher explore the primordial factors, such as customs, ethnicity, culture, religion and social groups that influence the dynamics of elections. Researchers found that Primordialism often influences voting behavior. This research too aims to find out how primordialism influences voting behavior in West Tanjungpinang District